2021
DOI: 10.3390/ani11072062
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Innately Preferred D-Limonene and Trans-Anethole Does Not Overcome Innate Aversion to Eucalyptol, Affecting Growth Performance of Weanling Piglets

Abstract: In the present research, two studies were performed to determine the effects of specific botanical compounds (BCs) on the innate feed preference and feed intake of piglets, as follows: Exp. 1 studied the innate feed preferences of post-weaning piglets using a double-choice feeding test. A total of 828 weaned piglets were distributed into 36 pens (23 pigs/pen) and assigned to three dietary pair choice feeding options (n = 12): unsupplemented prestarter diets (reference) versus reference plus D-limonene, trans-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Based on these theories, we designed this bitingballs test, it showed that these three compounds limonene, allicin and betaine do have positive impact on food consumption. And it is consistent with the results of our biting-balls test, indicating that limonene, allicin and betaine could stimulate the smell or taste receptors of M. salmoides and had a strong attraction effect (Reyes-Camacho et al, 2021). In addition, the attraction effects of different food attractants varied, which could be attributed to differences in the number of olfactory receptor genes responsible for detecting different odor molecules (Liu et al, 2021), resulting in different sensations or recognition capacities of olfactory and taste receptors to attractants in M. salmoides.…”
Section: Discussionsupporting
confidence: 90%
“…Based on these theories, we designed this bitingballs test, it showed that these three compounds limonene, allicin and betaine do have positive impact on food consumption. And it is consistent with the results of our biting-balls test, indicating that limonene, allicin and betaine could stimulate the smell or taste receptors of M. salmoides and had a strong attraction effect (Reyes-Camacho et al, 2021). In addition, the attraction effects of different food attractants varied, which could be attributed to differences in the number of olfactory receptor genes responsible for detecting different odor molecules (Liu et al, 2021), resulting in different sensations or recognition capacities of olfactory and taste receptors to attractants in M. salmoides.…”
Section: Discussionsupporting
confidence: 90%
“…This is largely due to the decreased phylogenetic distance between humans and swine as opposed to humans and rodents [38][39][40][41]. However, most research involving swine taste preference has been performed in young pigs or lactating sows that are ad libitum fed [42][43][44][45][46]. Some swine researchers cite that sorghum is an inferior grain when compared to corn because growing pigs have a reduced feed intake and average daily gain when fed a sorghum-based diet [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…There is little published research on adult pig preference on flavors [42,44]. Wang et al [44] examined if the supplementation of the feed of 52 large white lactating sows would impact flavor preference in their piglets. The study was conducted to address the insufficient feed intake of commercial sows during lactation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation